Evaluating the efficacy of short duration Mitomycin C in safe surgery system trabeculectomy combined with cataract surgery - Khandelwal, Rekha (Clin Ophthalmol, 2019)
Purpose: To compare the efficacy of 0.2 mg/ml Mitomycin C (MMC) applied for 1-minute versus 2-minutes in patients undergoing combined surgery for primary glaucoma coexistent with cataract. Materials and methods: This was a randomized controlled clinical trial of 63 patients operated on for primary glaucoma (POAG or PACG) with visually significant cataract. All patients underwent safe surgery system trabeculectomy with manual small incision cataract surgery (MSIC) and implantation of PC IOL. Patients were randomized into intra-operative MMC 0.2 mg/ml for 1-minute (study group) and MMC 0.2 mg/ml for 2-minutes (control group). Success was measured on the basis of two different intraocular pressure (IOP) goals (IOP ≤21 mmHg, IOP ≤18 mmHg) and mean IOP reduction from baseline at the end of 12 months. Results: At 12 months, significant decreases in mean IOP were observed in both groups (P<0.001).The mean IOP reduction was 31.33±9.06% in the study group, as compared to 43.32±9.38% in the control group (P<0.001). The overall success for IOP ≤21 mm Hg was 80.5% in the study group and 90.9% in the control group (P<0.05). Kaplan-Meier analysis showed an insignificant difference in overall success rates of the two groups. Conclusion: The IOP reduction with 2-minute MMC (0.2 mg/ml) is more effective than 1-minute MMC after 12 months. It offers a decrease in anti-glaucoma medications and substantial visual recovery in combined surgery done for primary glaucoma coexistent with cataract.